Appeareance & reality in politics - "Connolly, William E." (Cambridge, 1981)
I propose in this study, first, to examine a series of intimate con nections between the quest for personal identity, the construction of political interpretations, the performance of the welfare state, and the legitimacy of that state in the eyes of citizens to whom it is formally accountable through elections. Secondly, I hope to show that an interpretive approach to political inquiry, because of the nature of the institutional practices to be understood, provides the best basis for comprehending this complex web of connections. This text is situated where the philosophy of social science and political theory intersect; it is nourished by the belief that its particular point of concentration permits one to make a distinctive contribution to issues on both sides of this academic boundary.
Keywords: Political Science